Applied mathematical Modeling to Evaluate Students’Satistaction with online learning in Savannakhet University: https://doi.org/10.69692/SUJMRD0901197 - SAIYASAND, Saysamone; XAYACOCIE, Paxaykhone; PHOMMAKHANH, Kheuavanh; CHOUNLAMOUNTRY, Lattanamany; Chansamouth, Sithath (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This study is to study the satisfaction of students’ towards online learning in Savannakhet University which has 2 objectives: 1. To evaluate the satisfaction of students towards online learning, 2. To compare the satisfaction of students towards online learning. The sample group is 83 students in Savannakhet University. The study tool is to create a questionnaire from google from assessment in 5 levels by assessment through online system and data analysis in two ways: statistical method and mathematical modeling method Mathematical Modeling (Analytic Hierarchy Process: AHP). The results of the assessment of the satisfaction of students’ towards online learning can be ranked in order of satisfaction of the main factor and secondary factors in order. Overall, it was found that the main aspect of lesson content (A = 1.0768) followed by online learning (D = 1.0345) followed by the understanding of students’ in using Google meet (E = 1.0291), online learning activities (B = 0.9842) and student learning (C = 0.8474). The results of the evaluation matrix can be concluded that the level of satisfaction of students’ towards online learning in the analysis of five elements including the main content of lessons, online learning activities, student learning, online learning and students' understanding of using Google meet has a level of satisfaction equal to 3.4969